MENJADI PEMIMPIN MASA DEPAN: MEMBANGUN KARAKTER DAN KOMPETENSI SISWA SMK SASMITA JAYA 1 - Wijayanto, Budi Prabowo; Rosmiati, Eti; Ernawati, Neneng; Luthfie, Ocha Mardhina; Agustini, Paryani (Indonesian Collaboration Journal of Community Services (ICJCS), 2024)
Education is an invaluable investment for a nation, serving as the vanguard of its progress and prosperity. The future generations of a nation are shaped by the education they receive, and a strong educational foundation is essential for building a strong and resilient nation. When education is effectively managed, the outcomes are undeniably positive. It empowers a nation with the knowledge, skills, and moral compass to thrive in an ever-changing world. Character building lies at the heart of sustainable and enduring human development. It encompasses not only individual moral and ethical values but also leadership qualities, interpersonal skills, mental resilience, and the ability to adapt to diverse life situations. In a complex society like Indonesia, character building serves as a critical tool in navigating the myriads of social, economic, cultural, and environmental challenges. Vocational High School (SMK) students are the future skilled workforce, poised to enter the world of industry and business upon graduation. While technical skills are undoubtedly essential, leadership abilities are equally crucial in preparing them to become individuals capable of leading teams, innovating, and adapting swiftly to the ever-evolving work environment. Therefore, comprehensive leadership training is paramount for SMK students to nurture their leadership potential from an early stage